2018
DOI: 10.1158/1078-0432.ccr-17-1767
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma Patients' KIR and KIR-Ligand Genotypes Influence Clinical Outcome for Dinutuximab-based Immunotherapy: A Report from the Children's Oncology Group

Abstract: PURPOSE In 2010, a Children’s Oncology Group (COG) phase III randomized trial for high-risk neuroblastoma patients (ANBL0032) demonstrated improved event-free survival (EFS) and overall survival (OS) following treatment with an immunotherapy regimen of dinutuximab, GM-CSF, IL-2, and isotretinoin compared to treatment with isotretinoin alone. Dinutuximab, a chimeric anti-GD2 monoclonal antibody, acts in part via NK cells. Killer Immunoglobulin-like Receptors (KIRs) on NK cells and their interactions with KIR-li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 27 publications
2
51
1
1
Order By: Relevance
“…Moxetumomab pasudotox is a recombinant immunotoxin targeting CD22, composed of an immunoglobulin light‐chain variable domain and a heavy‐chain variable domain genetically fused to a truncated form of Pseudomonas exotoxin A . Moreover, antiglycolipid‐targeted therapy is showing great promise in the treatment of neuroblastoma; Dinutuximab, an antibody against ganglioside GD2, was approved in 2015 by the Food and Drug Administration and has been used as a second‐line treatment for children with high‐risk neuroblastoma . In addition, it was shown that the antitumor efficacy of Rituximab, a monoclonal antibody against CD20 currently approved for the treatment of recurrent/refractory follicular B‐cell non‐Hodgkin's lymphomas, can be strongly augmented by its conjugation to saporin .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moxetumomab pasudotox is a recombinant immunotoxin targeting CD22, composed of an immunoglobulin light‐chain variable domain and a heavy‐chain variable domain genetically fused to a truncated form of Pseudomonas exotoxin A . Moreover, antiglycolipid‐targeted therapy is showing great promise in the treatment of neuroblastoma; Dinutuximab, an antibody against ganglioside GD2, was approved in 2015 by the Food and Drug Administration and has been used as a second‐line treatment for children with high‐risk neuroblastoma . In addition, it was shown that the antitumor efficacy of Rituximab, a monoclonal antibody against CD20 currently approved for the treatment of recurrent/refractory follicular B‐cell non‐Hodgkin's lymphomas, can be strongly augmented by its conjugation to saporin .…”
Section: Discussionmentioning
confidence: 99%
“…39 Moreover, antiglycolipid-targeted therapy is showing great promise in the treatment of neuroblastoma; Dinutuximab, an antibody against ganglioside GD2, was approved in 2015 by the Food and Drug Administration and has been used as a second-line treatment for children with high-risk neuroblastoma. 40,41 In addition, it was shown that the antitumor efficacy of Rituximab, a monoclonal antibody against CD20 currently approved for the treatment of recurrent/refractory follicular B-cell non-Hodgkin's lymphomas, can be strongly augmented by its conjugation to saporin. 42 Interestingly, immunotoxin toxicity can be improved by coadministration with the chemotherapeutic drug fludarabine in lymphoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Учитывая способность NK-клеток к лизису клеток НБ [15] и их потенциальную активность в контексте алло-ТГСК [16], обсуждается эффективность иммуноадоптивной терапии с использованием NK-клеток. О роли KIR-рецепторов и их лигандов в иммунном ответе косвенно свидетельствует ассоциация их генотипа с исходом терапии у реципиентов ауто-ТГСК [17] К л и н и ч е с к и е н а б л ю д е н и я ших иммунотерапию [18]. Дополнительным аргументом в пользу применения KIR-несовместимых NK-клеток именно в контексте алло-ТГСК может послужить их способность индуцировать экспрессию HLA I класса [19], что делает клетки опухоли потенциально более чувствительными к воздействию антигенспецифичных Т-лимфоцитов.…”
Section: Discussionunclassified
“…High‐dimensional datasets such as RNA‐seq data describing changes in NK cell gene expressions NKR gene sequences, and protein expressions in single NK cells (e.g., CyTOF) provide detailed description regarding the involvement of NK cell populations in immune responses elicited by a viral infection or by an organ transplant. Data‐driven models are being increasingly applied to develop predictive computational frameworks to determine precision biomarkers in patients for optimizing NK cell and T cell responses in immunotherapies or organ transplants. However, a key challenge in this endeavor is to know what measured variables should be included in such computational models.…”
Section: Future Directionsmentioning
confidence: 99%